Pengaruh Komitmen Organisasi dan Budaya Organisasi terhadap Kinerja Karyawan dengan Organizational Citizenship Behavior sebagai Variabel Intervening pada PT Andalan Mitra Prestasi Kota Padang - Drevina Jenifer Lopez; Febsri Susanti (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of employee performance as a determinant of company productivity, emphasizing the role of organizational commitment and organizational culture in influencing performance both directly and indirectly through Organizational Citizenship Behavior (OCB). The objective is to analyze the effect of organizational commitment and organizational culture on employee performance, with OCB as an intervening variable at PT. Andalan Mitra Prestasi in Kota Padang. A quantitative approach with an explanatory design was used. The sample consisted of 66 employees selected through a saturated sampling technique. Primary data were collected using a five-point Likert scale questionnaire, while secondary data were obtained from the company’s internal documentation. Analytical techniques included validity and reliability tests, classical assumption tests, descriptive analysis, path analysis, and the Sobel test, with data processed using SPSS. The results show that organizational commitment has a significant effect on both OCB and employee performance, whereas organizational culture does not significantly affect either OCB or performance. However, OCB significantly influences employee performance and mediates the effect of organizational commitment on performance. These findings underscore the strategic role of extra-role behavior in strengthening the relationship between internal organizational factors and individual performance. The implications highlight the importance of reinforcing organizational commitment and developing OCB as part of a sustainable effort to improve employee performance.